2016 International Wireless Communications and Mobile Computing Conference (IWCMC) 2016
DOI: 10.1109/iwcmc.2016.7577100
|View full text |Cite
|
Sign up to set email alerts
|

ESR: Energy aware and stable routing protocol for WBAN networks

Abstract: Wireless body area network (WBAN) calls for a next generation in wireless networks. This new generation is designed to operate autonomously, to connect various medical sensors and appliances located on or inside a human body. Mobile WBANs have been designed, offering numerous practical and innovative services so that health care and quality of life can be improved. Thus, the equipment used in WBAN is usually mobile and autonomous which imposes high constraint on energy. That is, the energy efficiency must be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 16 publications
(18 reference statements)
0
29
0
Order By: Relevance
“…In [13] authors presented an energy-aware routing (EAR) protocol that is employed for Medicare systems. A change in network topology results in the rapid depletion of battery energy, which results in an overall reduction in network efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…In [13] authors presented an energy-aware routing (EAR) protocol that is employed for Medicare systems. A change in network topology results in the rapid depletion of battery energy, which results in an overall reduction in network efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…After then, the initially generated population is refurbished by using the firefly algorithm. H. With the help of the new population, the new cost function is evaluated by using the equation (4).…”
Section: Navpreet Kaur Samra Ramanpreet Kaurmentioning
confidence: 99%
“…The drawback of this proposed work was that the authors did not consider the results regarding the energy consumption. In [3][4], authors suggested a stable, dependable, intensity beneficial directing convention for versatile Wireless Body Area Networks. The main aim was to extract the extra vitality of hubs with an expansion to establish lifetime of network.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al [15] evaluated the performance of BANs with Co-LAEEBA (Cooperative Link Aware and Energy Efficient protocol for wireless Body Area networks) protocol. Smail et al [16] introduced energy-aware routing protocol for wireless networks with sustained structure. In This protocol they used a model with energy-efficient road link.…”
Section: Related Workmentioning
confidence: 99%